Practice of Shamanism: Traditional Healing Practices and Contemporary Transformations in Khandacakra Municipality, Kalikot - Adhikari, Kanshi Prasad (Academia Research Journal, 2024)
This study explores the practice of shamanism from traditional healing practices to contemporary interpretations in Khandacakra Municipality of Kalikot, Nepal. Utilizing both primary and secondary data, the research examines the socio-cultural and economic factors influencing this transformation. The findings reveal that traditional shamanic culture is in practice in the community, with a significant portion of the population regularly consulting shamans. However, modernization, education, and global cultural exposure are driving changes in these practices. Contemporary shamanism, characterized by a blend of traditional and modern therapeutic approaches, is gaining acceptance, particularly among younger generations. The study highlights the potential for integrating shamanic practices with modern healthcare to provide a holistic approach to health and well-being. Despite challenges such as skepticism from the younger generation and competition from modern healthcare providers, there is strong support for the continued relevance of shamanic practices. This research contributes to the understanding of how traditional practices adapt to modern contexts and offers recommendations for sustaining these practices in the face of ongoing cultural and social changes.